Expression of creative poetics by architects and painters through the motifs of fine art works in the journal Crteži from 1956 to 1965 - Antešević, Nebojša; Babić, Goran (Arhitektura i urbanizam, 2020)
The paper analyzes the motives and artistic expressions of the fine art works of selected architects and painters – teachers and associates at the Faculty of Architecture in Belgrade, published in the faculty journal Crteži (Drawings), in the period from 1956 to 1965. By the classification of fine art works of the entire journal edition were established the represented motives, on the basis of which their characterization was given, and a comparative analysis was carried out in relation to the creative poetics and sensibilities of architects and painters, who contributed the most to the conceptionof the journal through the ten issues. Although originating from various initiatives and creative sensibilities of faculty members in the fields of architecture and fine art in a wider generation range, the fine art works of their choice for one-year issues of journal, among which the dominant place is free-hand drawing, testify to the high qualitative expression and the variety of represented motifs.